Mechanical performance and corrosion behaviour of Zr-based bulk metallic glass produced by selective laser melting. (April 2020) - Deng, L.; Gebert, A.; Zhang, L.; Chen, H.Y.; Gu, D.D.; Kühn, U.; Zimmermann, M.; Kosiba, K.; Pauly, S.
Abstract: Nearly fully dense, glassy Zr52.5 Cu17.9 Ni14.6 Al10 Ti5 bulk specimens were fabricated by selective laser melting (SLM) and their behaviour during compressive loading, during wear testing and in a corrosive medium was investigated. Their performance was compared with as-cast material of the same composition. The additively manufactured samples exhibit a yield strength around 1700 MPa combined with a plastic strain of about 0.5% after yielding despite the residual porosity of 1.3%, which is distributed uniformly in the samples. The propagation of shear bands in the bulk metallic glass prepared by SLM was studied. The specific wear rate and the worn surfaces demonstrated that similar wear mechanisms are active in the SLM and the as-cast samples. Hence, manufacturing the glass in layers does not adversely affect the wear properties. The same holds for the corrosion tests, which were carried out in 0.01 M Na2 SO4 and 0.1 M NaCl electrolyte. The anodic polarization curves of SLM samples and as-cast samples revealed a similar corrosion behaviour. However, the SLM samples have a slightly reduced susceptibility to pitting corrosion and exhibit an improved surface healing ability, which might be attributed to an improved homogeneity of the additively manufactured glass. Graphical abstract: Unlabelled Image Highlights: Zr52.5 Cu17.9 Ni14.6 Al10 Ti5 glass with a relative density exceeding 98.7% is fabricated via selective laser melting (SLM). The samples deform plastically (about 0.5%) and have high yield strengths above 1700 MPa in compression. Microhardness maps of SLM specimens suggest structural homogeneity despite the complex thermal history. The wear performance and corrosion properties of the SLM samples are comparable to that of the as-cast glass. SLM allows fabrication of metallic glasses, which can withstand the conditions arising in real-world applications.